Plum lucky [compact disc, unabridged] - Evanovich, Janet (Evanovich, Janet. Stephanie Plum novel., 2008)
Stephanie finds herself in over her head with a caper involving thrice stolen money, a racehorse, a car chase and a bad case of hives--not to mention her grandmother playing the slots in Atlantic City using the stolen money!